Crowdfunding: new form of both investment opportunities and source of capital - Ahmad, Khaliq; Mohd Nor, Rizal; Ahmad Kamely, Aimadhuddin (IGI Global, 2020)
Crowdfunding is a new form of both investment opportunities and source of raising capital. The aim of this chapter is to explore the understanding of the newly invented crowdfunding, types of the existing platforms of the industry. Authors investigated crowdfunding platforms that are registered in securities commission Malaysia and Kapitalboost platform of Singapore and their mode of investment. Authors also looked in depth and reviewed a current literature on crowdfunding. An investment model of crowdfunding that will be suitable for the Muslim investors who are looking into an ethical investment that will contribute to the wellbeing of the societies as whole through Mudharabah and Musharakah investment. The findings explored that equity crowdfunding could bring more benefit and less harm to entrepreneurs. Consequently, there are two types of models that are based on equity-in and equity-out; hence, the chapter recommends the equity crowdfunding over the debt-based through Islamic investment method of Musharakah and Mudharabah investment.